Educating and training cadres and Party members in revolutionary ethics according to Ho Chi Minh’s ideology in the new era - the era of Vietnam’s striving for development - Bui Thi Can, Le Thi Thanh Hieu, Phan Huy Chinh, Pham Thi Binh, Le Thi Gai, Pham Thi Minh (Journal of Daoist Studies, 2026)
Abstract: Moral education for cadres and Party members constitutes a major policy orientation shared by many countries and nations worldwide. Ho Chi Minh, the great leader of the Vietnamese nation, throughout his lifelong revolutionary career, consistently set a shining moral example of a revolutionary wholeheartedly devoted to striving and sacrifice for the people, the country, and the nation. Ho Chi Minh regarded morality as the foundation and root of the revolutionary, as well as the source of revolutionary strength, likening it to the roots of a tree or the headwaters of a river. Only when revolutionaries are grounded in revolutionary morality can they successfully fulfill the noble revolutionary mission in the cause of national independence and socialism. This article analyzes the current state of applying Ho Chi Minh’s moral thought in the education and cultivation of revolutionary ethics among cadres and Party members. On that basis, it proposes several solutions to enhance the effectiveness of applying Ho Chi Minh’s moral thought in educating and fostering revolutionary morality for cadres and Party members in the new era of Vietnam’s national development and advancement.